Bahasa Gaul Di Media Sosial Dan Ancaman Terhadap Kebudayaan Bahasa Indonesia Pada Remaja - Nuraini Nuraini; Loudwig Agustinus Purba; Sherly Anggreni Hasari Br Ginting; Fitriani Lubis (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
The use of slang on social media has become common among Indonesian teenagers. However, the use of this slang raises concerns about the existence of the Indonesian language as a national cultural property. This article discusses how slang on social media can be a threat to Indonesian language culture in adolescents. In this article, the authors update that the continuous and increasingly widespread use of slang can reduce the quality of Indonesian used by teenagers. In addition, the use of slang can also change the mindset and attitude of teenagers towards Indonesian as the official language of the state. This article also discusses how teenagers can strengthen the existence of the Indonesian language by avoiding the use of slang on social media, enriching their knowledge of the Indonesian language, and increasing awareness of the importance of the Indonesian language as a national cultural treasure. Thus, this article can provide insight and better understanding of the influence of slang in social media on Indonesian language culture in adolescents.